Strategi Pengelolaan SDM pada UMKM Berbasis Teknologi Digital: Studi Kasus Pada Sektor Kreatif di Kota Medan - Mita, Merry Moy (Universitas Methodist Indonesia, 2025)
This qualitative case study explores human resource management (HRM) strategies implemented by digital-based creative micro, small, and medium enterprises (MSMEs) in Medan, Indonesia. Using in-depth semi-structured interviews, participatory observation, and document analysis, the research identifies key themes emerging from thematic analysis. Four major themes were found: (1) recruitment through personal networks, prioritizing trust over formal assessment; (2) informal competency development through learning-by-doing and internal mentoring; (3) adaptive performance management that relies on project outcomes rather than structured evaluation systems; and (4) employee retention strategies based on emotional bonds, flexible working arrangements, and creative freedom. While these approaches reflect the flexibility and interpersonal nature of creative MSMEs, they also reveal limitations, including the absence of structured HR systems, minimal investment in continuous training, and limited financial incentives to retain top talent. These findings highlight the need to balance the inherent flexibility of creative MSMEs with more systematic HR practices to sustain competitiveness in a rapidly changing digital environment. The study contributes to the literature by contextualizing the Resource-Based View (RBV) and dynamic capabilities theory within the creative MSME sector of a developing country. Practical implications include recommendations for MSME owners, policymakers, and support institutions to design integrated programs that combine technology adoption with human capital capacity building.